Digital Educational Technologies In The Modern World - Iroda Gayratovna Majidova (Euro Asian Journal Publishing, 2024)
This article provides information about the possibilities of using digital educational technologies in higher education institutions and the use of digital educational programs in the educational process.
Keywords: Digital education technology; distance education; class